x - y = 1 has an x - intercept of -1 and a y intercept of 1
Solution:
Let us check one by one
First line:
y = -x
Rearranging we get,
x + y = 0
Find x intercept:
Substitute y = 0
x + 0 = 0
x = 0
Find y intercept:
Substitute x = 0
0 + y = 0
y = 0
Thus this line doesnt have x - intercept of -1 and a y intercept of 1
Second line:
x - y = 1
Find x intercept:
Substitute y = 0
x - 0 = 1
x = 1
Find y intercept:
Substitute x = 0
0 - y = 1
-y = 1
y = -1
Thus this line doesnt have x - intercept of -1 and a y intercept of 1
Third line:
x - y = -1
Find x intercept:
Substitute y = 0
x - 0 = -1
x = -1
Find y intercept:
Substitute x = 0
0 - y = -1
y = 1
Thus this line has x - intercept of -1 and a y intercept of 1
Fourth line:
x + y = 1
Find x intercept:
Substitute y = 0
x + 0 = 1
x = 1
Find y intercept:
Substitute x = 0
0 + y = 1
y = 1
Thus this line doesnt have x - intercept of -1 and a y intercept of 1